Mechanocatalytic Depolymerization of Cellulose With Perfluorinated Sulfonic Acid Ionomers - Karam, Ayman; Amaniampong, Prince N.; García Fernández, José M.; Oldani, Claudio; Marinkovic, Sinisa; Estrine, Boris; De Oliveira Vigier, Karine; Jérôme, François (Frontiers in Chemistry, 2018)
Here, we investigated that the mechanocatalytic depolymerization of cellulose in the presence of Aquivion, a sulfonated perfluorinated ionomer. Under optimized conditions, yields of water soluble sugars of 90-97 % were obtained using Aquivion PW98 and PW66, respectively, as a solid acid catalyst. The detailed characterization of the water soluble fraction revealed (i) the selective formation of oligosaccharides with a DP up to 11 and (ii) that depolymerization and reversion reactions concomitantly occurred during the mechanocatalytic process, although the first largely predominated. More importantly, we discussed on the critical role of water contained in Aquivion and cellulose on the efficiency of the mechanocatalytic process.